Bilateral Agreement of Indonesia - Japan for Low Carbon Growth Cooperation: An Analysis of the Effectiveness and the Compliance Level - Chotimah, Hidayat Chusnul; Arisanto, Puguh Toko; Pratiwi, Tiffany Setyo (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2020)
To reduce greenhouse gas emissions, in 2013 Indonesia and Japan agreed to establish bilateral cooperation in Joint Crediting Mechanism (JCM). JCM facilitated and encouraged Japanese institutions (private and state) to cooperate with Indonesian institutions in a form of investment in low-carbon development. This article seeks to analyze the effectiveness of JCM implementation between Indonesia and Japan by using international cooperation effectiveness approach to determine the legal form whether soft law or hard law. The results show that both Indonesia and Japan choose to use soft law in this negotiation which has several benefits. Soft law provides an opportunity for both countries to achieve their goals and it can be used as a tool for negotiation and compromise. This article will also analyze the level of compliance between the two countries through coercion, reciprocity, reputation, and domestic institutions approaches. Authors found that there is no coercion in the form of sanction in implementing JCM; there is a reciprocity allowing JCM to provide financial assistance, transfer of technology and human resource; Indonesia and Japan keep their promises to uphold their international commitments; and domestic institutions play a role in promoting compliance in the low carbon growth partnership between the two countries.